Antiplatelet and Antithrombotic Activities of Non-Steroidal Anti-Inflammatory Drugs Containing an N-Acyl Hydrazone Subunit - Chelucci, Rafael Consolin [UNESP] (2014)
Nonsteroidal anti-inflammatory drugs (NSAIDs) 1-5 containing an N-acyl hydrazone subunit were prepared and their antiplatelet and antithrombotic activities assessed in vitro and in vivo. Compounds 1-5 inhibited the platelet aggregation induced by adenosine diphosphate and/or arachidonic acid, with inhibition rates of 18.0%-61.1% and 65.9%-87.3%, respectively. Compounds 1 and 5 were the most active compounds, inhibiting adenosine-diphosphate-induced platelet aggregation by 57.2% and 61.1%, respectively. The inhibitory rates for arachidonic-acid-induced platelet aggregation were similar for compound 2 (80.8%) and acetylsalicylic acid (ASA, 80%). After their oral administration to mice, compounds 1, 3, and 5 showed shorter mean bleeding times than ASA. Compounds 1 and 5 also protected against thromboembolic events, with survival rates of 40% and 33%, respectively, compared with 30% for ASA. In conclusion, these results indicate that these novel NSAIDs containing an NAH subunit may offer better antiplatelet and antithrombotic activities than ASA.